Separated-path Ramsey atom interferometer - Featonby, P; Summy, G; Webb, C; Godun, R; Oberthaler, M; Wilson, A; Foot, C; Burnett, K (1998)
We demonstrate a novel type of cesium atom interferometer which uses a combination of a microwave ground state transition and momentum changing adiabatic transfer light pulses as the atom optical components. It is the first atom interferometer where the mechanism which forms the internal superposition plays no part in spatially splitting the atomic wave packets. The coherence length of the atom source is found by measuring the spatial correlation between the two interferometer arms. This allows us to determine the temperature of the atomic ensemble.